2019
DOI: 10.6026/97320630015838
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modelling and docking analysis of pleurocidin (an antimicrobial peptide) like peptides with enterotoxin H from Klebsilla pneumonia

Abstract: Enterotoxin H is a key molecular target for replication and establishment of Klebsilla pneumonia in the host. Therefore, it is of interest to study the interaction of enterotoxin H with pleurocidin like peptides using molecular modelling (template PDB ID: 1YCE), Lig-Plot (ligand construction) and docking tools for therapeutic consideration. The hydrophobic pocket and the active site residues (Val 13, Met 16, Gly 25, Ala 25, and Ile 28) were identified using Cast P, Molegro and Sitehound tools. Docking results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Ho et al, 2016 revealed also the effect of an amidated hybrid of the flounder pleurocidin and the frog dermaseptin (P-Der) on the inhibition of the bacterial catabolic processes. In a separate investigation, the utilization of molecular modeling and docking analysis data revealed the ability of pleurocidin-like peptides to selectively target enterotoxin H derived from Klebsiella pneumoniae, which suggests the potential of these peptides to interact with Frontiers in Pharmacology frontiersin.org non-membrane components (Bupesh et al, 2019). Collectively, these reports provide strong support for the assertions regarding the impact of pleurocidin and its effects on diverse intracellular processes, including the induction of apoptosis.…”
Section: Frontiers In Pharmacologymentioning
confidence: 62%
“…Ho et al, 2016 revealed also the effect of an amidated hybrid of the flounder pleurocidin and the frog dermaseptin (P-Der) on the inhibition of the bacterial catabolic processes. In a separate investigation, the utilization of molecular modeling and docking analysis data revealed the ability of pleurocidin-like peptides to selectively target enterotoxin H derived from Klebsiella pneumoniae, which suggests the potential of these peptides to interact with Frontiers in Pharmacology frontiersin.org non-membrane components (Bupesh et al, 2019). Collectively, these reports provide strong support for the assertions regarding the impact of pleurocidin and its effects on diverse intracellular processes, including the induction of apoptosis.…”
Section: Frontiers In Pharmacologymentioning
confidence: 62%